Thermotherapy. An alternative for the Treatment of American Cutaneous Leishmaniasis (2012)
ABSTRACT: Background: Pentavalent antimonials (Sb5) and miltefosine are the first-line drugs for treating cutaneous leishmaniasis in Colombia; however, toxicity and treatment duration negatively impact compliance and cost, justifying an active search for better therapeutic options. We compared the efficacy and safety of thermotherapy and Meglumine antimoniate for the treatment of cutaneous leishmaniasis in Colombia. Method: An open randomized Phase III clinical trial was performed in five military health centres. located in northwestern, central and southern Colombia. Volunteers with parasitological positive diagnosis (Giemsa-stained smears) of cutaneous leishmaniasis were included. A single thermotherapy session involving the application of 50°C at the center and active edge of each lesion. Meglumine antimoniate was administered intramuscularly at a dose of 20 mg Sb5 /kg weight/day for 20 days. Results: Both groups were comparable. The efficacy of thermotherapy was 64% (86/134 patients) by protocol and 58% (86/149) by intention-to-treat. For the Meglumine antimoniate group, efficacy by protocol was 85% (103/121 patients) and 72% (103/143) by intention-to-treat, The efficacy between the treatments was statistically significant (p 0.01 and <0.001) for analysis by intention to treat and by protocol, respectively. There was no difference between the therapeutic response with either treatment regardless of the Leishmania species responsible for infection. The side effects of Meglumine antimoniate included myalgia, arthralgia, headache and fever. Regarding thermotherapy, the only side effect was pain at the lesion area four days after the initiation of treatment. Conclusion: Although the efficacy rate of Meglumine antimoniate was greater than that of thermotherapy for the treatment of cutaneous leishmaniasis, the side effects were also greater. Those factors, added to the increased costs, the treatment adherence problems and the progressive lack of therapeutic response, make us consider thermotherapy as a first line treatment for cutaneous leishmaniasis. Registered ClinicalTrials.gov NCT00471705